Viola minha viola: a obra violonística de Américo Jacomino, o Canhoto (1889-1928), na cidade de São Paulo - Estephan, Sérgio (2007)
This research work has, as main target, to analyse the violinistic work from the native of the city of São Paulo, Americo Jacomino, the Canhoto (the Left-handed), (1889-1928). For that we ll first reflect about the theoretic-methodological aspects that served as reference for this research work, where History and Music dialogue frequently. Then, we ll stand out its professional route, when he started his career in circus, theathers anda movie-theathers until he gets into the mainly concert rooms in São Paulo: The Teatro Municipal and the Conservatório Dramático e Musical . After that, we ll analyse his musical production from this phonographic file and scores, looking for a reflect, about his compositional universe. Finally, as reference, the Argentinean Tangos composed and intepreted by Canhoto we ll make an investigation about the guitar in the South American continent, from the approach of Canhoto and Carlos Gordel, as well between the Brazilian and the Argetinean Tango, to finish, talking about the Paraguayan Agustin Barrios, one of the most important violinist from the beginning of the Twentieth Century